Prognostic Significance and Clinical Application of MNS16A (VNTR) polymorphism in North Indian Lung Cancer Patiets - Kaur, Ishmeet (My University, 2024)
Background: Telomerase is critical in maintaining telomere integrity in normal and cancer cells, with hTERT being a key factor in telomere biology. The activity of hTERT is directly connected to cellular ageing and the development of various health issues, including cancer. The MNS16A polymorphism in the hTERT gene has been identified as an essential factor influencing telomerase activity and linked to cancer susceptibility, further highlighting the complexity of telomere-related genetics in cancer research. Although prior studies have examined this association, the results have varied significantly across populations. Purpose: We aimed to investigate the potential prognostic role of the MNS16A polymorphism in the hTERT gene among lung cancer patients in the North Indian Population. Experimental Design: In this study, we genotyped 401 lung cancer samples, all undergoing platinum-based chemotherapy, for the MNS16A polymorphism using PCR to explore its association with lung cancer risk. Overall survival of lung cancer patients was evaluated using the univariate Kaplan-Meier method, while Cox regression analysis was used to calculate the adjusted hazard ratio. Stratified analyses were conducted to assess risks for subgroups based on various clinicopathological parameters, clinical outcomes, and toxicity, with odds ratios (ORs) and 95% confidence intervals (CIs) being calculated. A p-value of less than 0.05 was considered statistically significant in all analyses.
Keywords: Telomerase; hTERT; Lung Cancer; Survival